The application of augmented reality in elementary school education (Research, Society and Development, 2021)
The application of Augmented Reality in the education sector has increased, the novelty of Augmented Reality technology has become a special attraction for stake holders to improve the quality of education. However, so far there is still a lack of literature studies that focus on investigating the application of Augmented Reality to students at the basic education level. This study presents a literature review on the use of Augmented Reality technology to students at the basic education level. Articles that were synthesized from 2010 to 2020 indexed by Google Schoolar were 10 articles. Using qualitative content analysis, this study attempts to answer two questions; (1) What is the impact of the application of Augmented Reality on the learning outcomes of Elementary School Students? and (2) how does the Pedagogic Perspective view Augmented Reality?